Influence of the Immune Checkpoint Inhibitors on the Hemostatic Potential of Blood Plasma - Patalakh, Iryna; Wandersee, Alexandra; Schlüter, Julian; Erdmann, Michael; Hackstein, Holger; Cunningham, Sarah (Transfusion Medicine and Hemotherapy, 2024)
Introduction: Immune checkpoint inhibitors (ICIs) have revolutionized classical treatment approaches of various cancer entities, but are also associated with a number of side effects. One of these may be life-threatening clotting disorders with the risk of thrombotic or hemorrhagic complications, the mechanisms of which are still poorly understood. In the present study, we analyzed the direct effects of pembrolizumab, nivolumab, and ipilimumab on platelet aggregation as well as plasma coagulation followed by fibrinolysis in an ex vivo model. Methods: Microplate spectrometry was used to analyze aggregation, coagulation, and fibrinolysis in platelet-free (PFP) and platelet-rich (PRP) healthy donor plasma samples treated with pembrolizumab, nivolumab, ipilimumab, and appropriate isotype controls. Aggregation was induced by TRAP-6. Clotting of PFP and PRP followed by lysis was initiated with a tissue factor in a mixture of phosphatidylserine:phosphatidylcholine and the addition of t-PA. Among other parameters, the area under the curve (AUC) was used to compare the effect of ICIs on aggregation, coagulation, and fibrinolysis. Results: Upon direct contact with platelets, pembrolizumab stimulated platelet aggregation in PRP, while nivolumab and ipilimumab promoted disaggregation with corresponding changes in the AUC. Pembrolizumab and nivolumab, both PD-1 receptor inhibitors, had no effect on the plasma coagulation cascade. Ipilimumab, a CTLA-4 receptor inhibitor, significantly increased the rate of PRP clotting. When clotting was followed by lysis, all ICIs were found to prolong the growth of the PRP-derived fibrin clot and delay its elimination. This was manifested by an increase in AUC relative to control PRP. Conclusion: This study characterizes the potential impact of pembrolizumab, nivolumab, and ipilimumab on hemostasis. Nivolumab and ipilimumab are able to reduce aggregation and increase the procoagulant properties of platelets, which can cause side effects associated with hemostatic imbalance leading to thrombosis or bleeding. The observed ICI-specific effects may contribute to our understanding of the mechanisms by which ICI affects platelets and suggest how, in a clinical setting, to reduce coagulation disorders during ICI treatment in the future
Keywords: Immune checkpoint inhibitors; Aggregation; Coagulation; Fibrinolysis; Platelet-rich plasma; Platelets; Thrombocytes